Antimicrobial effect and biocompatibility of novel metallic nanocrystalline implant coatings. Issue 8 (21st August 2015) - Gosau, Martin; Haupt, Michael; Thude, Sibylle; Strowitzki, Martin; Schminke, Boris; Buergers, Ralf
Abstract: Aim: The present in vitro study was designed to evaluate the surface characteristics, biocompatibilities and antimicrobial effects of experimental titanium implant surfaces, coated by nanocrystalline silver, copper, and bismuth. Biocompatible and antimicrobial implant modifications could result in reduced biofilm formation on implant surfaces and therefore in less periimplant inflammation. Findings: Titanium discs (thickness 1 mm and 12 mm in diameter) were coated by pulsed magnetron‐sputtering of nanocrystalline metals (bismuth, copper, and silver). Bismuth coatings revealed higher surface roughness values in comparison to silver and copper coatings via atomic force microscopy. Ion release after 168 h in culture medium was analyzed by inductively coupled plasma‐mass spectrometry and showed significant different amounts of released copper (>120 000 µg/L), silver (550 µg/L) or bismuth (80 µg/L). No cytotoxic effect on HaCaT cell proliferation was detected on the uncoated Ti/TiO2 reference surfaces, the bismuth coatings and silver coatings. In contrast, copper‐coated discs showed a strong cytotoxic effect. All three coatings exhibited antimicrobial effects by trend in the fluorometric Resazurin testing and significant localized antibacterial effects in live/dead microscopy after incubation of the specimens for 150 min in bacterial solution of S. epidermidis . Conclusions: The tested metallic implant coatings (silver and bismuth) allowed surface modifications that may improve therapeutic approaches to biofilm prevention on dental implants. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 2015. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 104B: 1571–1579, 2016.